Mechanical regulation of the Notch signaling pathway - Suarez Rodriguez Freddy; Sanlidag Sami; Sahlgren Cecilia (Elsevier Ltd., 2025)
The mechanical regulation of Notch signaling is an emerging area of interest in cell biology. Notch is essential in many physiological processes in which mechanical stress plays an important role. This review provides an overview of the mechanoregulation of Notch signaling in multiple steps of the pathway. First, we discuss the current knowledge on the direct mechanoregulation of Notch receptor maturation and localization to the membrane and the effect of mechanical stress on the Notch components. Next, we explore how ligand-receptor interactions and membrane dynamics are possible subjects to mechano-regulation, emphasizing the role of cytoskeletal interactions, membrane stiffness, and endocytic complex formation. We further delve into the necessity of tension generation for negative regulatory region (NRR) domain unfolding, facilitated by ligand endocytosis and other microforces. Additionally, we examine the indirect mechano-regulation of S2 and S3 cleavages. Finally, we discuss the mechanoregulation of the Notch intracellular domain (NICD) trafficking and nuclear entry and the impact of mechanical stress on heterochromatin dynamics and nuclear NICD interactions. This review aims to draw attention to the intricate interplay between mechanical cues and Notch signaling regulation, offering novel insights into the multifaceted nature of cellular mechanobiology.